Blockade of Dickkopf (DKK)-1 induces fusion of sacroiliac joints. Issue 3 (19th March 2009) - Uderhardt, S; Diarra, D; Katzenbeisser, J; David, J-P; Zwerina, J; Richards, W; Kronke, G; Schett, G
Abstract : Objective: To study whether Dickkopf (DKK)-1, an inhibitor of wingless (Wnt) signalling, is involved in the fusion of sacroiliac joints. Methods: Mice transgenic for tumour necrosis factor (TNFtg mice), which develop bilateral sacroiliitis, were treated with vehicle, anti-TNF antibody or anti-DKK1 antibody. Sacroiliac joints were analysed for histological signs of inflammation, bone erosion, osteoclast formation and ankylosis. Moreover, expression of collagen type X, β-catenin and DKK-1 was assessed by immunohistochemistry. Results: There were no signs of spontaneous ankylosis of the sacroiliac joints in TNFtg mice. TNF blockade effectively reduced inflammation, bone erosion and osteoclast numbers in the sacroiliac joints, but did not lead to ankylosis. Blockade of DKK1 had no effect on inflammatory signs of sacroiliitis, but significantly reduced bone erosions and osteoclast counts. Moreover, DKK1 blockade promoted expression of collagen type X, the formation of hypertrophic chondrocytes and ankylosis of sacroiliac joints. Conclusion: DKK1 influences inflammatory remodelling of sacroiliac joints by prevention of joint ankylosis. This may indicate an important role of the Wnt signalling pathway in the structural bone changes of axial joint disease. Although this model does not reflect the entire spectrum of ankylosing spondylitis in humans, it helps to explain the pathophysiological processes of sacroiliac joint ankylosis, which is a hallmark of the spondyloarthritides.